Opportunistic infections among schoolchildren who were on antiretroviral therapy in Ethiopia: a systematic review and meta-analysis - Birhanu, Molla Yigzaw; Telayneh, Animut Takele; Kassie, Abere; Tegegne, Eniyew; Jemberie, Selamawit Shita (Frontiers in Pediatrics, 2024)
Introduction: the most common and severe cause of morbidity and mortality among HIV-positive children is opportunistic infections. All HIV-infected children are at risk of developing a variety of opportunistic infections. The healthcare workers, programmers and other stakeholders are in doubt to use the onset and predictors of opportunistic infections (OIs) among schoolchildren on ART due to the presence of conflicting results found from the primary studies. The extracted data were exported to Stata TM Version 17.0 for further management and analysis. The presence of heterogeneity across studies was checked using the chi square test and quantified using I 2 test. Various methods, including forest plots, publication bias assessment, sensitivity tests, subgroup analysis, and meta-regression, were employed to determine the source of heterogeneity, but none were successful. The overall onset of OIs was estimated via pooling the incidence of primary studies using a random effects Meta-Analysis model. The predictors were identified using Meta-regression and the presence of significant association was declared using a p-value of 0.05 with 95% CI. The strength of association was reported using an adjusted hazard ratio with 95% CI.Results: Eleven studies were included in this systematic review and meta-analysis. The onset of OIs among schoolchildren on ART in Ethiopia was 5.58 (95% CI: 4.50, 6.67) per 100 children-Years of OIs-free observations. Those children who had no parents had 1.41 (95% CI: 1.10, 1.80) times higher chance of getting OIs when compared with those children having one or both parents.Children who had poor ART adherence had 2.96 (95% CI: 1.66, 5.29) times higher chance of experiencing OIs than children who had good ART adherence. Finally, the chance of experiencing OIs among rural children was 2.15 (95% CI: 1.63, 2.83) times higher than their counterparts in Ethiopia.Conclusions: Three in every thirty-three schoolchildren on ART developed OIs in Ethiopia.Predictors of OIs included schoolchildren without parents, those with poor adherence to ART, and rural residents. This suggests that social support, medication adherence, and access to healthcare services may play important roles in preventing and controlling OIs among schoolchildren living with HIV in rural areas.